2018
DOI: 10.1038/s41386-018-0271-x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal raphe serotonin neurons inhibit operant responding for reward via inputs to the ventral tegmental area but not the nucleus accumbens: evidence from studies combining optogenetic stimulation and serotonin reuptake inhibition

Abstract: The monoamine neurotransmitter serotonin (5-hydroxytryptamine; 5-HT) exerts an inhibitory influence over motivation, but the circuits mediating this are unknown. Here, we used an optogenetic approach to isolate the contribution of dorsal raphe nucleus (DRN) 5-HT neurons and 5-HT innervation of the mesolimbic dopamine (DA) system to motivated behavior in mice. We found that optogenetic stimulation of DRN 5-HT neurons enhanced downstream 5-HT release, but this was not sufficient to inhibit operant responding for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…We and others have shown that the optogenetic activation of DRN 5-HT neurons elicits antidepressant-like effects in mice and rats [31,43]. In addition to mental disorders, many reports have demonstrated that 5-HT neurons are involved in reward processing [8][9][10][11][32][33][34][35]. Some reports have shown that the activation of DRN 5-HT neurons elicits reward-related behaviors including self-stimulation and real-time place preference [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that the optogenetic activation of DRN 5-HT neurons elicits antidepressant-like effects in mice and rats [31,43]. In addition to mental disorders, many reports have demonstrated that 5-HT neurons are involved in reward processing [8][9][10][11][32][33][34][35]. Some reports have shown that the activation of DRN 5-HT neurons elicits reward-related behaviors including self-stimulation and real-time place preference [9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous reports have demonstrated that the activation of DRN 5-HT neurons induces an antidepressant-like effect in mice and rats [30,31]. Similar to an antidepressive effect, rewarding potency of DRN 5-HT neurons has been studied by using several lines of genetically-modified mice [9][10][11][32][33][34][35]. Liu et al and Li et al have shown that sucrose intake activates DRN 5-HT neurons and that the activation of DRN 5-HT neurons causes operant reinforcement using ePet1-Cre mice [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…5‐hydroxytryptamine is an important neurotransmitter for both addiction and itch. Serotoninergic projection from dorsal raphe nucleus (DRN) of the midbrain with the DRN being the primary brain region containing neurons positive for 5‐HT, DRN 5‐HT neurons exert an inhibitory influence over operant responding for reward through a direct interaction with the mesolimbic DA system at the level of the VTA . Decreases in serotonin synthesis have also been observed during chronic nicotine exposure .…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 99%
“…5‐HT elicited itch when applied to human or mouse skin at lower doses . In addition, serotoninergic projection from DRN to IC and serotonergic signalling in the rostral ventromedial medulla (RVM) is involved in acute itch sensation processing in mice . Moreover, serotoninergic neurons in the brainstem nucleus raphe magnus (NRM) send descending projections to the spinal cord .…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 99%
“…SSRIs generally provoke a decrease in motivated behaviors for reward. This is mediated by the inhibitory effect of increased 5-HT on dopaminergic neurons in the ventral tegmental area ( Sanders et al., 2007 ; Browne et al., 2019 ). Similar reductions in motivation are observed with SNRIs ( Stromberg et al., 2002 ; Simon O’Brien et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%